Treatment Approach Analysis of Hospitalized Patients with Liver Cirrhosis; A Prospective Observational Study: Pharmaceutical Science-Pharmacy practice - Karimi Mir, Azardokht; P. Pawar, Atmaram; Kumar Panda, Bijoy (International Journal of Life Science and Pharma Research, 2022)
The analysis of medications prescribed for managing patients with liver cirrhosis provide essential insight into appropriate therapeutic regimens and prevents inappropriate therapeutic outcomes. This study aimed to analyze the treatment approach of hospitalized patients with liver cirrhosis and identify drug-drug interactions (DDIs) and hepatic dose adjustment associated with treatment. A prospective observational study was conducted for 12 months in the Medicine Department of Bharati Hospital and Research Center, located in Pune, India. Medication charts of 113 patients who were diagnosed with cirrhosis were reviewed. Pharmaceutical care-related standard tools were applied to identify DDIs and medications requiring hepatic dose adjustment. Investigating the number of complications showed that ascites (40.7%) were the most common complication associated with liver cirrhosis. The treatment approach analysis revealed that antibiotics (23.6%), diuretics (22.5%), and analgesics (13.8%) were the most frequently prescribed pharmacological class of medications. The most commonly identified DDIs was an interaction between Mefenamic Acid-Furosemide (46.3%). In addition, approximately half of prescribed Paracetamol (48.1%) required its dose to be adjusted according to the patient's liver function test. Therefore, periodic analysis of prescribed medications needs to be performed since the inappropriate selection of medications can further lead to drug-related problems like DDIs or hepatic dose adjustment. Our findings provide feedback to prescribers to improve the appropriate selection of medications and enhance patient safety.